Efektivitas Layanan Bimbingan Kelompok dengan Menggunakan Teknik Acceptence and Commitment untuk Mengurangi Gaya Hidup Konsumtif - Asbi, Asbi; Hasibuan, M Fauzi; Sari, Mawar (Program Studi Bimbingan dan Konseling FKIP UMSU, 2022)
This study aims to test the effectiveness of group guidance services using acceptance and commitment techniques to reduce the consumptive lifestyle of students. This study uses a quantitative method of Quasi Experiment type with The Non Equivalent Control Group design. The research subjects were second semester students of Guidance and Counseling Study Program, Faculty of Teacher Training and Education, where second semester students of Class B were the experimental group and class A students were the control group. The research instrument is a consumptive lifestyle questionnaire with a Likert Rating Scale model. Analysis of research data was carried out by means of the Wilcoxon Signed Rank Test and the Kolmogorov Smirnov 2 Independent Sample test. The results of the study revealed that the effectiveness of group guidance services using the acceptance and commitment technique was effective in reducing the consumptive lifestyle of guidance and counseling study program students. This can be seen from the difference in the posttest results of the experimental group which is greater than the posttest of the control group.